2010
DOI: 10.1098/rsif.2010.0417
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis can take plant-parasitic nematodes to the source of a chemo-attractant via the shortest possible routes

Abstract: It has long been recognized that chemotaxis is the primary means by which nematodes locate host plants. Nonetheless, chemotaxis has received scant attention. We show that chemotaxis is predicted to take nematodes to a source of a chemo-attractant via the shortest possible routes through the labyrinth of air-filled or water-filled channels within a soil through which the attractant diffuses. There are just two provisos: (i) all of the channels through which the attractant diffuses are accessible to the nematode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 36 publications
5
64
0
1
Order By: Relevance
“…Once the plasmodium is formed, it begins to optimise the number and length of tubules connecting the two food sources. This approach is not maze-solving by chemotaxis as reported previously in slime moulds (Adamatzky, 2012) and nematodes (Reynolds et al, 2011); the shortest path in our maze is constructed entirely by feedback within the maze-spanning plasmodium (Nakagaki et al, 2000;Nakagaki et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Once the plasmodium is formed, it begins to optimise the number and length of tubules connecting the two food sources. This approach is not maze-solving by chemotaxis as reported previously in slime moulds (Adamatzky, 2012) and nematodes (Reynolds et al, 2011); the shortest path in our maze is constructed entirely by feedback within the maze-spanning plasmodium (Nakagaki et al, 2000;Nakagaki et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of ambiguous CO 2 emissions, it is largely unknown what triggers the attraction of plant parasitic nematode towards host plants (discussed by Rasmann et al, 2012, this issue). Carbon dioxide has been shown to attract several nematode species (Klingler, 1963;Dusenbery, 1980Dusenbery, , 1987Pline and Dusenbery, 1987), but aggregation and attraction of plant parasitic nematodes also have been demonstrated in response to plant root exudates (Prot, 1980;Rolfe et al, 2000;Curtis et al, 2009;Reynolds et al, 2011). Only recently, has it been found that plant parasitic nematodes follow gradients of herbivore-induced terpene volatile organic compounds (Ali et al, 2011).…”
Section: Management Of Plant Parasitic Nematodes Using Root-produced mentioning
confidence: 93%
“…However, they have potential negative impacts on the environment and human health resulting from their toxic residues. As general awareness of the harmful effects of chemical nematicides has increased, their use has been prohibited in some areas, and farmers have reduced the use of these chemical nematicides (Reynolds et al, 2011;Elbadri et al, 2008;Pandey et al, 2000). Therefore, to overcome these problems, there is a great need for effective and environmentally friendly alternatives to control root-knot nematodes.…”
Section: Introductionmentioning
confidence: 99%
“…The typical symptoms of infected plants include galls and knots in the roots of plants, wilting, and yellowing of aboveground foliage from insufficient nutrient uptake (Adekunle and Akinlua, 2007;Siddiqui et al, 2011). These nematodes result in yield losses equating to billions of US dollars worldwide every year (Reynolds et al, 2011). For managing the presence of this pest on cultivated crops, chemical nematicides are usually more effective than other strategies.…”
Section: Introductionmentioning
confidence: 99%